Computerized tomography based 3D modeling of the clavicle. Issue 7 (14th June 2016) - Lambert, Simon; Al‐Hadithy, Nawfal; Sewell, Mathew David; Hertel, Ralph; Südkamp, Norbert; Noser, Hansrudi; Kamer, Lukas
ABSTRACT: Previous studies have suggested clavicular morphology is highly variable, particularly in the lateral retrocurved section. Current clavicle fracture plating systems require three dimensional intra‐operative contouring to achieve adequate fit and necessitate variable soft tissue dissection placing fracture perfusion and muscular attachments at risk. The aim of this study was to search for a surgically relevant superficial shape pattern. This is a retrospective CT‐based analysis of 174 non‐pathological clavicles in 95 adults (45 females, 50 males). Using the principle of cylindrical parameterisation generated 3‐D computer models, we identified an implant preferred pathway (IPP), defined as a continuous linear region where the least possible soft tissue disruption would be necessary for plate fixation. The IPP mean form was within 3.04 mm (SD ± 1.34) on all clavicles. Clavicle length, and not shape, was found to be the biggest variable (correlation between size and form co‐ordinates r  = 0.99, p  < 0.05), accounting for 79% of overall variability. This length variation was mainly located in the medial antecurved section. Superior convexity and recurvatum were the main shape variables, however they only contributed 8% and 5% to the overall variation, respectively. Three IPP lengths were shown to match all clavicles when aligned at the acromial end first. In contrast to previous studies, we have shown that the IPP is fairly consistent with respect to the general shape with the exception of length variation which mainly affected the medial antecurved section. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1216–1223, 2016. CLINICAL RELEVANCE: Future pre‐contoured fracture fixation systems should provide variable length plates with a constant lateral section retrocurve and a variable medial antecurve.